2021
DOI: 10.4018/ijide.2021040103
|View full text |Cite
|
Sign up to set email alerts
|

How Sustainable Marketing Strategies Apply Digital Economy Innovations in Cyber Marketing and Digital Communications for Colleges

Abstract: Cyber marketing, digital communications, and social media practices for branding and marketing purposes have allowed colleges and universities to engage in sustainable/green marketing. For colleges, this means reducing advertising, marketing, and promotions costs in conjunction with lessening previous environmental impacts of printing, paper waste, mailing brochures, and college recruiter travel and transportation. Digital economy innovations in cyber marketing create channels for advertising and promotion wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The experimental data were analyzed with methods such as deterioration analysis, cluster analysis and component analysis [27], qualitative content analysis [28], and entropy approach [8]. For the systematic review studies, systematic literature review [29,30], meta-analysis [10,11], thematic analysis [31][32][33], content analysis [34,35], and descriptive statistics [21] were used.…”
Section: Methods Of Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental data were analyzed with methods such as deterioration analysis, cluster analysis and component analysis [27], qualitative content analysis [28], and entropy approach [8]. For the systematic review studies, systematic literature review [29,30], meta-analysis [10,11], thematic analysis [31][32][33], content analysis [34,35], and descriptive statistics [21] were used.…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…[25] found that green marketing has raised consumer awareness of the environment, and social media has proved to be an effective tool to make internet users aware of green products and their advantages. On the other hand, some studies focused on certain platforms for digital marketing, such as Instagram [28] and websites [35]. Ref.…”
Section: Positive Effects Of Digital Media On Green Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…As given by Osborne Chambers and Thompson (2024), the theory posits that successful change involves first preparing the organization to accept that change is necessary (Unfreeze), implementing the change (Change), and then solidifying the new processes as the standard (Refreeze). The benefit is that Lewin's model provides a clear and easy-tounderstand framework emphasizing the significance of preparing for change (Burrell et al, 2023). This preparatory stage helps to reduce resistance and anxiety, making the transition smoother.…”
Section: Lewin's Change Management Modelmentioning
confidence: 99%
“…This preparatory stage helps to reduce resistance and anxiety, making the transition smoother. The model's simplicity makes it widely applicable across various organizational changes (Burrell et al, 2023). The critique of the model is the critique: Critics argue that Lewin's model may need to be revised for today's complex and rapidly evolving business environment.…”
Section: Lewin's Change Management Modelmentioning
confidence: 99%